Practical considerations for endurance training with power - Jones, S. (ASPETAR Sports Medicine Journal, 2016)
Records show that human power measurement was first performed well over 100 years ago in the laboratory. However, it took another 80 years for the power meter to evolve into an accurate measuring tool, useable in the field, then a further 10 years for the data to be understood, stored and analysed in a format that could be easily interpreted.